Nonsyndromic impacted triple supernumerary teeth in the maxilla, including single dens in dente malformation: a case report with a two-year follow-up - Šarčev, Ivan; Petronijević Šarčev, Branislava; Mirković, Siniša (Vojnosanitetski pregled, 2022)
Introduction. Mesiodens is a midline supernumerary tooth, mostly located in the maxillary arch. We presented a rare case of a patient with nonsyndromic impacted triple supernumerary teeth precluding the eruption of central maxillary incisors. Case report. In addition to providing a detailed 3D picture of the patient’s dentition, cone-beam computed tomography (CBCT) scan analysis revealed dens in dente malformation of one of the supernumeraries. Following surgical removal of all supernumerary teeth, the maxillary central incisors erupted spontaneously after a two-year period. Conclusion. To the best of our knowledge, no similar case report has been published in scientific literature. This case report highlights the importance of CBCT for proper diagnosis of supernumerary teeth as well as additional anomalies.